MINIMASI BIAYA DISTRIBUSI BERAS MISKIN DENGAN METODE NORTH WEST CONER PADA PERUM BULOG SUBDIVRE III SURAKARTA - Indiana Maharani Putri; Bebas Widada; Elistya Rimawati (Jurnal Ilmiah SINUS, 2018)
BULOG has a duty to distribute subsidized rice for low-income society groups, which is realized in the implementation of Raskin (Beras Miskin) program, but BULOG Subdivre III Surakarta has not thought about the cost of transporting Raskin quite a lot, because the most important is the Raskin demand from all districts / City. The purpose of this study is to apply the North West Corner (NWC) method to determine the cost of Raskin distribution in Perum BULOG Subdivre III Surakarta, in order to facilitate the user in determining the initial solution and determining the allocation of the transportation. The North West Coner (NWC) method is expected to minimize the cost of Raskin distribution. The data computed is January 2017 data with distribution fee of Rp 908,444,756. The results of NWC implementation showed the results of the manual calculations significantly, NWC program, and software QM for Windows 3 is the same that is Rp 903.088.837. The calculation results prove the reduction of the cost of Rp 5.355.919 or 0.58% if applying the NWC Method. The North West Corner method can be the initial solution to minimize the cost of Raskin distribution in Perum BULOG Subdivre III Surakarta.